Improving strength to woman handball players - Cazan, F.; Georgescu, A. (Science, Movement & Health, 2017)
Aim. The development of strenght can not only be done to become strong. On the contrary, the purpose of force development is to serve specific needs in a certain sport (more possibly in any other sports game, in handball), to develop specific force or combinations to increase the performance of athletes to the highest possible level. A senior handball player performs about 50 to 60 jumping on average on and without ball, with and without finishing in attack and defense, the motor skills typically being carried out with the load of their own weight with and without possession of the ball, with external presence in Direct body combat with the opponent in rhythm and tempo imposed by alternating the playing phases. For these reasons, we consider strenght a fundamental component in the handball game and must be carefully prepared and valued. Methods. The subjects of the research are 18, components of the women's handball team Neptun Constanta, with an average age of 26.94 ± 3.78 years, team working in the National League, League I. In the initial testing, subjects were subjected to anthropometric measurements, then after a 20-minute warming consisting of stretching, light running, run-and-school elements (jogging up, running with swinging back, running with swinging forward) , Stepped step, stepped step, step added, crossed step, etc.), gymnastics, accelerated running, sprints, the subjects underwent the following tests in this order: -testing the force of lower limbs, abdomen, upper limbs: 1-abdominal force: repeats in 30 seconds 2-long jump 3- squats with heavy weighting : a maximum repeat 4- pull-ups: maximum number of repetitions 5-flat bench press: a maximum repeat In the 12 weeks (July 1 - September 20, 2016) of the two tests, the Neptun Constanta team had included in the training program the training program we designed to optimize the force Results. The parameter values recorded in the two initial and final tests differ statistically significantly from 5 parameters in 5, which means a proportion of 100% of the tests. At these parameters, following the verification of statistical hypotheses using Test t, the null hypothesis was rejected, the significance threshold (p) being calculated being less than 0.05. Parameter averages calculated for final testing indicate an improvement in the athletes' preparation for initial testing at all samples. Statistical scatter indicators: standard deviation, amplitude and variance coefficient, we can say that the handball team Neptun Constanþa is homogeneous in relation to this parameter category. Conclusions. The basic finding of this paper is that the force of the subjects has increased, which confirms the hypothesis that by carrying out a rigorously standardized program based on specific strength exercises, the level of training of the driving force will increase. For the development of detention it is necessary to act either by increasing the maximum force or by increasing the contraction rate of the muscles or by combining these two working directions. It can work alternately or simultaneously. The coach should know the shortcomings of each athlete and set the rules for transforming the maximum force into explosive force.